Developing Business Model Based On Islamic Classical Economic Thoughts - Nadhirah Nordin; Nur Amani Aisyah Samsuddin; Rahimah Embong; Azlin Alisa Ahmad; Rossidi Usop; Siti Khatijah Ismail; Suraya Ismail (Richtmann publishing, 2024)
Indexed by SCOPUS/ERA